The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/00016357.2016.1272000
|View full text |Cite
|
Sign up to set email alerts
|

Operator-related aspects in endodontic malpractice claims in Finland

Abstract: Operator-related factors had no impact on endodontic malpractice claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Unfortunately, many dentists seem to leave several details unrecorded. However, the level of documentation has improved in the last years (21), which was also seen as an improvement in documentation of the use of root canal irrigants and medicaments in our study. Still, none of the documents scrutinized gave any information about the method of the application of root canal irrigants and medicaments (ie, syringe or not and, in case of syringe, the type of needle used).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Unfortunately, many dentists seem to leave several details unrecorded. However, the level of documentation has improved in the last years (21), which was also seen as an improvement in documentation of the use of root canal irrigants and medicaments in our study. Still, none of the documents scrutinized gave any information about the method of the application of root canal irrigants and medicaments (ie, syringe or not and, in case of syringe, the type of needle used).…”
Section: Discussionsupporting
confidence: 65%
“…In 2011 to 2016, PIC handled an annual average of 7700 claims, 700 of which were related to dental care, but no detailed information about the types of injuries is given in the PIC official statistics. Previous research reports from Finland have shown that endodontics predominate in dental malpractice claims in the 2000s, reaching up to 200 claims annually (20,21). A recent report from the United States describes a similar increasing trend in dental malpractice cases from 2004 to 2014 (22).…”
Section: Introductionmentioning
confidence: 83%
“…We can, however, infer that the perforations were massive or otherwise serious since the majority of the cases resulted in tooth extraction. A further limitation is that these data cannot answer the question about the reasons leading to accidental perforations because the quality of the patient documents varied widely [21], and consequently, descriptions of the incidents or attempts to repair them varied from detailed to minor or none.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to observe these conducts may lead to lawsuits in which the operator can be held liable for material, moral and aesthetic damages, since the expert literature reports that Endodontics is one of the dental specialties frequently cited in prevalence judicial process research in Dentistry (Pinchi et al, 2013;Caputo et al;Zanin et al;Vehkalahti & Swanljung, 2017).…”
Section: Discussionmentioning
confidence: 99%